Analisis Kuantitatif Pengaruh Kegiatan Ekstrakurikuler terhadap Prestasi Belajar Siswa Kelas 10 SMA Negeri 1 Krian - Oktarina, Risma Putri; Wardani, Rahma Kusuma; Desviandy, Fadlillah Anggun; Syaputra, Raditya Eko; Putra, Rizki Bayu Anggara; Wulandari, Ayu (Lembaga Yasin AlSys, 2025)
This study was conducted to analyze the impact of extracurricular activities on the academic performance of Grade X students at SMA Negeri 1 Krian, located in Sidoarjo Regency, East Java. The background of this research highlights the importance of developing a relevant and comprehensive educational vision to improve the quality of education in Indonesia, particularly in preparing students to face global challenges. Education should not only serve as a source of knowledge but also foster creativity, work ethic, and broader perspectives in students so that they can make positive contributions to society. In this study, we employed a quantitative approach with a correlational design to evaluate the relationship between students' participation in extracurricular activities (variable X) and their academic performance (variable Y). The research population consisted of 37 Grade X students, selected randomly through a random sampling method. Data collection was conducted using a Google Form-based questionnaire designed with a four-point Likert scale: strongly disagree, disagree, agree, and strongly agree. Data analysis was performed descriptively to provide an overview of the collected data and inferentially using normality tests and t-tests to assess the relationship between the two variables. The findings of this study are expected to provide new insights into the impact of extracurricular activities on students' academic performance at SMAN 1 Krian. These findings aim to assist the school in designing more effective and comprehensive extracurricular programs that not only enhance students' non-academic potential but also support their academic success. Furthermore, this research is anticipated to make a significant contribution to educational reform in Indonesia, especially in optimizing the role of extracurricular activities as a means of holistic student development. Through a comprehensive approach, this study strives to support the achievement of an educational vision that is relevant, sustainable, and responsive to the challenges of the current era of globalization. Additionally, the results of this research can serve as a reference for schools in creating more inclusive and student-oriented extracurricular programs tailored to the needs of the learners.